2016
DOI: 10.1063/1.4942885
|View full text |Cite
|
Sign up to set email alerts
|

Graphene-oxide-semiconductor planar-type electron emission device

Abstract: Graphene was used as the topmost electrode for a metal-oxide-semiconductor planar-type electron emission device. With several various layers, graphene as a gate electrode on the thin oxide layer was directly deposited by gallium vapor-assisted chemical vapor deposition. The maximum efficiency of the electron emission, defined as the ratio of anode current to cathode current, showed no dependency on electrode thickness in the range from 1.8 nm to 7.0 nm, indicating that electron scattering on the inside of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 28 publications
2
17
0
Order By: Relevance
“…Their detailed fabrication processes were described elsewhere. 11 The electron emission characteristics were measured in a vacuum chamber at the pressures of 10, 10 À4 , and 10 À6 Pa evacuated by a turbomolecular pump and/or a scroll pump, respectively. An anode electrode of a metal plate for applying a voltage of 1 kV was placed 5 mm away from the gate electrode.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Their detailed fabrication processes were described elsewhere. 11 The electron emission characteristics were measured in a vacuum chamber at the pressures of 10, 10 À4 , and 10 À6 Pa evacuated by a turbomolecular pump and/or a scroll pump, respectively. An anode electrode of a metal plate for applying a voltage of 1 kV was placed 5 mm away from the gate electrode.…”
Section: Methodsmentioning
confidence: 99%
“…In our previous study, a high emission current density of 1-100 mA/cm 2 was achieved by suppressing the inelastic electron scattering within the topmost gate electrode using a graphene gate electrode, while maintaining a relatively high electron emission efficiency of 0.1%-1%, which is 2 orders of magnitude higher than the conventional MOS planar-type electron emission devices. 11 In this study, detailed electron emission properties of the graphene-oxide-semiconductor (GOS) type planar electron emission device (e.g., operating vacuum pressure dependence and stability of electron emission current) and further improvement of its electron emission properties by vacuum annealing are discussed.…”
Section: Introductionmentioning
confidence: 99%
“…The current density is calculated by dividing the anode current by the electron emission area of the device structure. It was already confirmed that the electron emission occurs at whole area of the electron source [28]. Therefore, the designed emission area can be considered as the real emission area.…”
mentioning
confidence: 86%
“…These excellent features of graphene suggest the ideal material for the gate electrode of the MOS type electron emission source. In fact, the efficiency of planar-type electron sources has been improved to 0.3~13 % by suppression of electron scattering using graphene gate electrode [27][28][29][30][31][32]. However, further improvement of the electron emission efficiency of the planar-type electron emission source has been required to obtain sufficient electron beam current from an emission area equivalent to the electron source sizes of the conventional electron guns.…”
mentioning
confidence: 99%
“…For example, Ga vapor is an effective catalyst in graphene nanoribbon synthesis from an amyloid fibrils template, and the width of nanoribbon is controlled only by the width of pristine template 26 . Large-area graphene can be synthesized with methane CVD combining Ga vapor 28 , 29 . Monolayer graphene can also be readily produced on the Ga surface since the solubility of carbon in Ga is negligible 22 , 31 .…”
Section: Introductionmentioning
confidence: 99%